Substitusi Tepung Porang Pada Olahan Cookies Sehat: Substitute Porang Flour in Healthy Cookies - Ni Putu Ragita Cahya WIcaksani, Ni Putu Ragita Cahya Wicaksani; Damiati; Ni Wayan Sukerti (Jurnal Kuliner, 2023)
This study aims to find out; 1) the formula used in making porang flour substitution syringe cookies and 2) the quality of porang flour substitution syringe cookies. This study used a pre-experimental method by adapting a one-shot case study model. There were 20 panelists involved in this study consisting of 4 lecturers in the Culinary Arts Vocational Education (PVSK) study program, Ganesha Education University, and 16 culinary teachers at Vocational High School (SMK). The panelists were selected using totally sampling technique. Data were collected using observation techniques. The instruments used in this study are; observation sheet. The data that has been collected is then analyzed using a t-test, especially one sample t-test. The results showed that; 1) The formula used to make syringe cookies using 80% porang flour and 20% wheat flour, with a formulation of 200-grams porang flour, 50-grams wheat flour, 200-grams margarine, 150-grams refined sugar, 25-grams milk powder, 25-grams cornstarch, 1/4 tsp vanilla powder; 2) The quality of syringe cookies in the good category in terms of three aspects, namely; t-count value of 20 where t-table is 2.086 and size effectiveness value is 1.0 (good) for texture; t-count value of 19.47 where t-table is 2.086 with size effectiveness value of 0.97 (good) for color; and t-count value of 20 where t-table is 2.086 with effectiveness value size of 1.0 (good). Keywords: Porang flour; Healthy Cookies; Syringe Cookies.